Selective Enhancement of the Cell-Permeabilizing Activity of Adenylate Cyclase Toxin Does Not Increase Virulence of Bordetella pertussis - Holubova, Jana; Juhasz, Attila; Masin, Jiri; Stanek, Ondrej; Jurnecka, David; Osickova, Adriana; Sebo, Peter; Osicka, Radim (International journal of molecular sciences, 2021)
The whooping cough agent, Bordetella pertussis, secretes an adenylate cyclase toxin-hemolysin (CyaA, ACT, or AC-Hly) that catalyzes the conversion of intracellular ATP to cAMP and through its signaling annihilates the bactericidal activities of host sentinel phagocytes. In parallel, CyaA permeabilizes host cells by the formation of cation-selective membrane pores that account for the hemolytic activity of CyaA. The pore-forming activity contributes to the overall cytotoxic effect of CyaA in vitro, and it has previously been proposed to synergize with the cAMP-elevating activity in conferring full virulence on B. pertussis in the mouse model of pneumonic infection. CyaA primarily targets myeloid phagocytes through binding of their complement receptor 3 (CR3, integrin αMβ2, or CD11b/CD18). However, with a reduced efficacy, the toxin can promiscuously penetrate and permeabilize the cell membrane of a variety of non-myeloid cells that lack CR3 on the cell surface, including airway epithelial cells or erythrocytes, and detectably intoxicates them by cAMP. Here, we used CyaA variants with strongly and selectively enhanced or reduced pore-forming activity that, at the same time, exhibited a full capacity to elevate cAMP concentrations in both CR3-expressing and CR3-non-expressing target cells. Using B. pertussis mutants secreting such CyaA variants, we show that a selective enhancement of the cell-permeabilizing activity of CyaA does not increase the overall virulence and lethality of pneumonic B. pertussis infection of mice any further. In turn, a reduction of the cell-permeabilizing activity of CyaA did not reduce B. pertussis virulence any importantly. These results suggest that the phagocyte-paralyzing cAMP-elevating capacity of CyaA prevails over the cell-permeabilizing activity of CyaA that appears to play an auxiliary role in the biological activity of the CyaA toxin in the course of B. pertussis infections in vivo.
Keywords: Adenylate Cyclase Toxin; fagocyty; Sheep; adenylate cyclase toxin; AMP cyklický; Humans; Host-Pathogen Interactions; interakce hostitele a patogenu; Female; permeabilita buněčné membrány; Virulence; myši inbrední BALB C; lidé; Bordetella pertussis; zvířata; virulence; myši; Cyclic AMP; pertuse; Mice; Phagocytes; ženské pohlaví; pore-forming activity; Cell Membrane Permeability; lung inflammation; RTX toxin; Whooping Cough; lung colonization; Animals; adenylátcyklasový toxin; cAMP intoxication; Mice, Inbred BALB C; ovce